High levels of C-reactive protein are associated with an increased risk of ovarian cancer: results from the Ovarian Cancer Cohort Consortium - Peres, LC; Mallen, AR; Townsend, MK; Allen, NE (American Association for Cancer Research, 2019)
Growing epidemiologic evidence supports chronic inflammation as a mechanism of ovarian carcinogenesis. An association between a circulating marker of inflammation, C-reactive protein (CRP), and ovarian cancer risk has been consistently observed, yet, potential heterogeneity of this association by tumor and patient characteristics has not been adequately explored. In this study, we pooled data from case-control studies nested within six cohorts in the Ovarian Cancer Cohort Consortium (OC3) to examine the association between CRP and epithelial ovarian cancer risk overall, by histologic subtype and by participant characteristics. CRP concentrations were measured from pre-diagnosis serum or plasma in 1,091 cases and 1,951 controls. We used multivariable conditional logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs). When CRP was evaluated using tertiles, no associations with ovarian cancer risk were observed. A 67% increased ovarian cancer risk was found for women with CRP concentrations >10mg/L compared to <1mg/L (OR=1.67, 95% CI=1.12, 2.48). A CRP concentration >10mg/L was positively associated with risk of mucinous (OR=9.67, 95% CI=1.10, 84.80) and endometrioid carcinoma (OR=3.41, 95% CI=1.07, 10.92), and suggestively positive, though not statistically significant, for serous (OR=1.43, 95% CI=0.82, 2.49) and clear cell carcinoma (OR=2.05, 95% CI=0.36, 11.57; p-heterogeneity=0.20). We noted heterogeneity by oral contraceptive use (p-interaction=0.003), where the increased risk was present only among ever users (OR=3.24, 95% CI=1.62, 6.47). The present study adds to the existing evidence that CRP plays a role in ovarian carcinogenesis, and suggests that inflammation may be particularly implicated in the etiology of endometrioid and mucinous carcinoma.